Ankylosing spondylitis: description of the clinical case from the position of the international classification of functioning, life and health limitations - R. R. Akhunova; G. R. Akhunova (Klinicist)
Objective: to describe the clinical case of a patient with ankylosing spondylitis (AS) with an assessment of the functioning of his body taking into account the clinical situation, environmental factors and personal factors from the standpoint of the international classification of functioning, life and health limitations.Materials and methods. The patient, 26 years old, was hospitalized in the Department of therapy with complaints of periodic aching pain in the lumbar and cervical spine at rest; aching pain in the ankle and knee joints when moving; heel pain when walking; morning stiffness in the spine lasting 30 minutes; weight loss to 11 kg. over the past year. The patient was evaluated laboratory parameters, electrocardiography, echocardiographic examination, ultrasound examination of hepatobiliary zone and kidneys, radiography of pelvic bones, lumbar spine, ankle, knee, foot joints, magnetic resonance imaging of sacroiliac joints.Results. During the examination, a clinical diagnosis was established: as. Formed rehabilitation diagnosis: b280.3, b710.2, b780.1, b130.1, b134.0, b455.3, s760.1, s740.0, s750.1, d230.2, d410.3, d450.3, d850.1, d760.1, d920.2, d475.2, which fixed the patient has intense pain, moderate violations of mobility in the spine, a short morning stiffness, mild depression, severe fatigue; minor violations in the structure of the lumbar spine, knee and ankle joints and joints of the foot; moderate difficulties in maintaining activity during the day, expressed functional disorders, expressed difficulties in walking, minor difficulties in performing paid work, minor difficulties in spending time with family and friends, moderate difficulties in recreation and leisure, moderate difficulties in driving.Conclusion. This clinical case demonstrates the possibility of using ICF in clinical practice on the model of a patient with as, which allows a comprehensive look at the patient and quantify the condition of the patient, to form a common language for the work of a multidisciplinary team to determine the further stage of rehabilitation of patients.